Impact of pediatric inflammatory bowel disease on caregivers' work productivity: A multicenter study by the SEGHNP - Velasco Rodríguez‐Belvís, Marta; Palomino, Laura; Pujol Muncunill, Gemma; Martin‐Masot, Rafael; Muñoz Codoceo, Rosa Ana; Barrio Torres, Josefa; Navas-López, Víctor Manuel; Martín de Carpi, Javier (Wiley, 2024)
Objectives/Background: Pediatric inflammatory bowel disease (PIBD) poses significant challenges not only to patients but also to their families, particularly affecting the work productivity of caregivers. This Spanish multicenter study aims to elucidate the extent of this impact. Materials and Methods: A cross‐sectional, multicenter study was conducted between February 2021 and June 2023, involving parents or caregivers of PIBD patients aged 10–18 years. The study utilized the Work Productivity and Activity Impairment (WPAI) questionnaires alongside assessing disease activity and socioeconomic status to quantify work productivity loss and its economic implications. Results: The study included 370 patients from 37 centers, highlighting a significant loss of work productivity among caregivers, especially mothers. The global unemployment rate was notably higher in this group compared to national averages (22.9% vs. 13.8%), particularly among females (30.7% vs. 13.7%), with absenteeism and presenteeism rates (26.4% and 39.9%) significantly impacting the caregivers’ ability to work. The study also identified active disease and treatment with biologics or steroids as risk factors for increased work productivity loss. Conclusions: Caregivers of children with inflammatory bowel disease face considerable challenges in maintaining employment, with a notable economic impact due to lost work hours. The findings underscore the need for targeted support and interventions to assist these families, suggesting potential areas for policy improvement and support mechanisms to mitigate the socioeconomic burden of PIBD on affected families.
Keywords: Niños - Enfermedades; Niños - Cuidado; Intestinos - Enfermedades; Enfermedades crónicas; Absentismo laboral; Pediatría - Investigación; Absenteeism; Children; Chronic illness; Presenteeism; WPAI